The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.wear.2006.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of micro-abrasion–corrosion of UNS S30403, S31603 and S32760 stainless steels

Abstract: In this study, the synergistic effects of abrasion and corrosion on UNS S30403, S31603 and S32760 stainless steels have been investigated using a micro-abrasion test rig. The stainless steel samples have been studied under both pure abrasion (PA) and abrasion-corrosion (AC) conditions simulated by using silicon carbide based slurries in either distilled water or 3.5% sodium chloride solutions. Tests have been conducted at various abrasive concentrations (0.006-0.238 g/cm 3 ) and at 38 and 180 m sliding distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 32 publications
(41 reference statements)
1
43
0
4
Order By: Relevance
“…Celis et al [26] caution against simple analysis of monitoring the surface open circuit potential (OCP) during tribo-corrosion tests as this analysis requires in-depth understanding of the mechanical, chemical Tribo-corrosion mechanism regime map. Data points used are taken from [42,43,65,66]. and electrochemical effects on OCP.…”
Section: Wear-corrosion Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Celis et al [26] caution against simple analysis of monitoring the surface open circuit potential (OCP) during tribo-corrosion tests as this analysis requires in-depth understanding of the mechanical, chemical Tribo-corrosion mechanism regime map. Data points used are taken from [42,43,65,66]. and electrochemical effects on OCP.…”
Section: Wear-corrosion Interactionsmentioning
confidence: 99%
“…Recent research has shown that this solution has difficulties, as Souza and Neville [41] and Bello et al [42] and Thakare et al [43] show, the performance of WC-Co-Cr systems can suffer localized corrosion of the carbide phases, thereby compromising the performance of such surfaces as well as the importance of composition and integrity of Cr based passive films.…”
Section: Tribo-corrosion Of Different Coating Typesmentioning
confidence: 99%
“…Reports have also been made where the synergy results seemed to be dependent more on techniques and test conditions adopted during the tests as well as the impact of corrosive solution, the material property, and also the type of materials itself. For most alloys and metal samples the most significant impact was found at a mild corrosive environment [25], [26], [34], [40]- [44].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Bello, Wood and Wharton [34] on UNS S30403, S31603 and S32760 stainless steel, they attempted to evaluate the synergistic effects of micro-abrasion-corrosion using three approaches. They used two-body, mixed and three-body abrasion methods.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos estudos via modelagem e da investigação experimental feita para avaliar as interações entre os danos mecânicos e corrosivos, as falhas dos materiais pela ação combinada desses fenômenos ainda não são totalmente compreendidas [9]. Alguns ensaios de abrasão e corrosão separadamente são realizados, com associação desses fenômenos através de tratamento matemático posterior, mas eles apresentam muita dispersão e erros [10]. A fim de se obter resultados mais precisos, o ensaio deve incluir o efeito combinado.…”
Section: Introductionunclassified